Bimbingan Teknis (BIMTEK) Pemeliharaan Ayam Kampung Unggul Balitbangtan (KUB-2) di Praya Barat Lombok Tengah - Tamzil, Mohammad Hasil; Budi Indarsih; Sasongko. W. Rusdianto (Universitas Mataram, 2024)
Technical Guidance Activities (BIMTEK) aim to provide prospective farmers with knowledge about the management of raising KUB chickens, and the related aspects to raising KUB chickens. The activity was carried out in collaboration with various parties, including: West Nusa Tenggara Agricultural Instrument Standards Implementation Center (BPSIP), Central Lombok Agriculture Service, Mataram University Faculty of Animal Science, and the KUB Chicken Farmer Groups which were spread across all villages in Central Lombok. BIMTEK activities were carried out in the West Praya office hall, Central Lombok, from 8.30 to 13.00 Central Indonesian Time. The implementation of BIMTEK used short talk and discussion methods. Activities went smoothly as planned. Thus it can be concluded that BIMTEK activities can provide additional insight to all participants about the KUB chicken management system. In order for the understanding of raising KUB chickens to be fully understood, intensive assistance needs to be provided once the project has started.